الإمام مجد الدين أبو البركات عبد السلام ابن تيمية الحراني وكتابه منتقى الأخبار: Biography of al-Imām Majdu al-Dīn Abū al-Barakāt 'Abdu al-Salām Ibn Taimiyyah al-Ḥarrānī and His Book Muntaqā al-Akhbār - Aḥmad bin Muḥammad bin ‘Abdul Hādī; Muhammad Yusram (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aims to introduce one of the leading scholars in fiqh and hadith, Majdu al-Din Abu al-Barakat Abdu al-Salam Ibn Taymiyyah al-Harrani al-Hanbali and introduce his book al-Muntaqa. Among the objectives of this research are to remind the ummah and the students about the greatness of his position which may not be known by many people as well as to read the biographies of the role model of the ummah by imitating and following in the footsteps of his life journey. It also explains one of the most important literature in the hadith al-ahkam, namely muntaqa al-akhbar. In this study, the researchers employed a descriptive approach. Among the most important results of this research are that Imam Majdu al-Din Ibn Taymiyyah was born in Harran in 590 AH and died there in 653 AH. Majdu al-Din Abu al-Barakat is an expert in many disciplines including fiqh, hadith, al-nahw, al-qira'at, and ushul al-fiqh. He studied with many scholars and had traveled to Baghdad several times to recite knowledge in front of the scholars. Abu Al-Barakat wrote many books among which his phenomenal books are al-Muntaqa min al-Ahkam. His reason for writing the book was a request of a judge, Bahauddin bin Shaddad, to Imam Majd al-din to write it in Aleppo. The scholars differed in determining the name of this book and the strongest opinion is al-muntaqa fi al-akhbar fi al-ahkam. This book has many prominences yet does not free from some criticism even though it is in a small number. Abu Al-Barakat has quoted many references in his book. The scholars have an interest in this book by explaining its contents in the form of writing and lectures.